Unlocking the potential of metal-organic frameworks-based mixed matrix membranes for hydrogen separation and purification - Ahmad N.N.R.; Lee Y.; Abdul Hamid M.R.; Mohd Ghazi T.I.; Nasir R.; Leo C.P.; Koh S.P.; Pasupuleti J.; Tiong S.K. (Korean Society of Industrial Engineering Chemistry, 2024)
Membrane-based separation is a promising technology for hydrogen separation and purification due to its low energy consumption. Conventional membranes, such as polymeric membranes, often suffer from permeability-selectivity trade-offs weakening their potential for challenging gas separations. Metal-organic frameworks (MOFs) with uniform apertures, high porosities, large internal surface areas, and tunable functionalities make them excellent fillers in mixed matrix membranes (MMMs) fabrication for hydrogen separation. This review evaluates current state-of-the-art MMMs performances, explores the challenges in MMMs fabrication, and discusses current strategies in MOF-based MMMs fabrication and modification aspects to enhance the membrane performance, specifically for H2/CO2, H2/CH4, and H2/N2 separation. Moreover, the hydrogen separation performance of MOF-based MMMs at elevated temperatures and pressure and improvement in antiaging and antiplasticization properties are discussed in detail. The outlook and perspectives for MOF-based MMMs for hydrogen separation are also provided. This review offers insight into the potential of MOFs as porous fillers in MMMs fabrication for hydrogen separation application. 2023 The Korean Society of Industrial and Engineering Chemistry